An Exploratory Review of Whole Life Cycle Costing for Malaysia Property Development - Mat Noor, Noorsidi Aizuddin; Eves, Chris; Abdul Mutalib, Noor Faizah (Journal of Techno-Social, 2012)
The demand of implementing Whole Life Cycle Costing (WLCC) towards property development has increased since the launch of Value Management Circular 3/2009 by the Economic Planning Unit Malaysia. The circular made compulsory for all public construction projects and programmes including property development estimated more than RM 50 Million to conduct WLCC. However, a knowledge gap on WLCC approach still exists and becomes a barrier among the practitioners in Malaysia particularly in property development industry. The main focus of this paper is to explore and disclose the necessary requirement to ensure the WLCC approach can be implemented successfully in Malaysia such as other developed countries. This research has been done by reviewing and analysing all the related empirical researches and supported with surveys among twenty property managers in Malaysia. As a result, structured evaluation documents and indicators have been determined to be considered in Malaysia property development decision making process.